Simultaneous non-invasive gas analysis in artificial photosynthesis reactions using rotational Raman spectroscopy. Issue 19 (1st September 2022) - Schwarz, Jesper; Ilic, Aleksandra; Kaufhold, Simon; Ahokas, Jussi; Myllyperkiö, Pasi; Pettersson, Mika; Wärnmark, Kenneth
Abstract : A new instrument for gas analysis in artificial photosynthesis reactions is presented. The device uses rotational Raman spectroscopy to analyse multiple gases (H2, O2, N2, CO, CO2 ) simultaneously, non-invasively and with short analysis times (15 s). Abstract : Optimising reactions in artificial photosynthesis research requires screening of many reaction and operation parameters, which is often resource-intense and time-consuming. In this paper, we demonstrate the use of a rotational Raman-based spectrometer for non-invasive quantification of several gases (H2, O2, N2, CO, CO2 ) with short analysis times (15 s), enabling high throughput screening. Furthermore, with this device, reaction progress can be monitored in situ, by real-time simultaneous quantification of multiple gases. We have applied this instrument and developed a method to study the O2 dependency of a prototypic light-driven hydrogen evolution reaction, showcasing the value of this approach for the artificial photosynthesis community in general.